KEPRIBADIAN TOKOH UTAMA DALAM NOVEL PASOLA KARYA MARIA MATILDIS BANDA (KAJIAN PSIKOANALISIS SIGMUND FREUD) - Kore Tome, Adelvina Juliaty; Robot, Marselus; Nurhuda, Aris (Pendidikan Bahasa dan Sastra Indonesia Universitas Nusa Cendana, 2025)
This study aims to describe the personality of the main character, Waleka, in Pasola, a novel by Maria Matildis Banda, through the lens of Sigmund Freud’s psychoanalytic theory. This theory emphasizes three structures of personality, id, ego, and superego which dynamically interact in shaping human behavior. The research employs a descriptive qualitative method with a reading-and-note-taking technique. The primary data source is the novel Pasola by Maria Matildis Banda, while secondary sources consist of relevant books, journals, and previous studies. The findings reveal that Waleka’s personality is predominantly influenced by the id aspect, manifested in his desires for power, polygamy, and the preservation of social prestige. The ego aspect is reflected in his efforts to adapt to the social environment through rational justifications of his actions, whereas the superego emerges in the form of guilt and remorse for past mistakes. These three aspects interact to form a complex personality dynamic, illustrating an inner conflict between instinctual drives, moral awareness, and sociocultural pressures within the main character.